Prolonged antibiotic therapy increased necrotizing enterocolitis in very low birth weight infants without culture-proven sepsis - Zhu, Keran; Gao, Hui; Yuan, Liping; Wang, Lili; Deng, Fang (Frontiers in Pediatrics, 2022)
Objectives: Our objectives were to identify factors associated with necrotizing enterocolitis (NEC) and to assess associations between the initial empirical antibiotic therapy (IEAT) duration, antibiotic therapy duration/hospital stays ratio (A/H ratio) before NEC and subsequent NEC in VLBW less than 32 weeks without culture-proven sepsis. Methods: A retrospective study was conducted by NICU of the First Affiliated Hospital of Medical University of Anhui province from June 2015 to December 2019, 414 VLBW infants less than 32 weeks were included in the present study. We divided the VLBW into NEC infants and no-NEC infants according modified Bell’s criteria. We used descriptive statistics to identify factors associated with NEC, and multivariate analyses to evaluate associations between IEAT duration, A/H ratio and NEC. Results: Of 414 VLBW neonates admitted to our center, 407 survived till out of the hospital. 36 infants (8.70%) suffered from NEC. Infants who suffered from NEC had a longer total parenteral nutrition time, total enteral nutrition time, IEAT duration and a larger A/H ratio than no-NEC infants. In multivariate analyses adjusted for the other factors, IEAT duration was associated with increased odds of NEC (OR=2.504, 95%CI 1.101,5.696); A/H ratio was associated with increased odds of NEC (OR=10.458, 95%CI 2.509, 43.593). For A/H ratio, the area under curves was 0.716 and the ideal cutoff was 0.373, and the sensitivity and specificity were 0.844 and 0.548, respectively. Conclusion: Prolonged antibiotic therapy might increase the risk of NEC in VLBW infants less than 32 weeks and should be used with caution.